Black Theater, Black Performance - Peixoto, Jordana Dolores; de Lima Silva , Renata (Revista Brasileira de Estudos da Presença, 2022)
This article discusses the concept of Black Performance, which, associated with the Black Movement, consists of a set of expressive manifestations, from ritual to spectacle, which scenically organize modes of existing and resisting of the black people in the African diaspora. The methodological design consists in an approach from macro to micro elements, starting with a general definition of Black Movement, then questioning the concept of Black Performance as a category that can encompass both traditional ritualistic performances and artistic performances in the languages of theater, dance and performing art. Finally, Black Theater is considered as the focus of analysis based on its historical aspects.